CRIMINAL EVIDENCE AUCTION SYSTEM AT THE ACEH BESAR DISTRICT PROSECUTOR'S OFFICE BASED ON ISLAMIC LAW’S PERSPECTIVE - Putri Raihan Wirda; Rahmad Efendy Al Amin Siregar; Azka Amalia Jihad (JURISTA: Jurnal Hukum dan Keadilan, 2025)
This article aims to analyze the suitability of the Aceh Besar District Attorney's Office's practice of auctioning evidence of criminal acts by the principles contained in the bai' muzayadah contract. This study employs a qualitative approach with a descriptive analysis method, as well as an empirical juridical approach, to evaluate the implementation of positive law and Sharia norms in the context of auctions. The results of the study indicate that the auction mechanism applied, including the open bidding-based e-auction system, generally reflects the principles of justice, openness, and transparency that are the basis for the validity of the bai' muzayadah contract. However, there are still challenges, such as unclear ownership documents for confiscated goods and determining limit prices that have the potential to cause elements of gharar. Essentially, the implementation of this auction can be considered valid under both Islamic law and positive law and contributes to the restoration of the economic value of confiscated goods and their utilization for the public good. The auction of evidence by the Aceh Besar District Attorney's Office has great potential to support the integration of sharia values ​​ in the sustainable governance of public assets.